2003
DOI: 10.1143/jjap.42.6772
|View full text |Cite
|
Sign up to set email alerts
|

Interference Effect on the Phase of Franz–Keldysh Oscillations in GaAs/AlGaAs Heterostructures

Abstract: We have studied photoreflectance spectra of GaAs/Al 0:3 Ga 0:7 As heterostructures from the viewpoint of the phase of Franz-Keldysh (FK) oscillations. The phase of the FK oscillations originating from the GaAs buffer layer shifts with the change of the Al 0:3 Ga 0:7 As-layer thickness, while the period does not vary. The FK-oscillation phase does not depend on the pump power, which suggests that the phase shift is not caused by a difference in the magnitude of modulation. We propose a calculation model for FK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In order to analyze the phase shift, we generalize the line-shape function of the FKOs. As previously reported, 15,16 the presence of the overlayer causes the interference of the probe beam, which leads to the phase shift of the FKOs. Next, we calculate the line shape of the FKOs using Eqs.…”
Section: Application To the Evaluation Of The Cat-cvd Of Sin Xsupporting
confidence: 61%
See 1 more Smart Citation
“…In order to analyze the phase shift, we generalize the line-shape function of the FKOs. As previously reported, 15,16 the presence of the overlayer causes the interference of the probe beam, which leads to the phase shift of the FKOs. Next, we calculate the line shape of the FKOs using Eqs.…”
Section: Application To the Evaluation Of The Cat-cvd Of Sin Xsupporting
confidence: 61%
“…Furthermore, we also discuss the line shape of the FKOs from the as-grown i-GaAs/ n-GaAs structure, especially focusing on the phase factor. As previously reported, 15,16 the analysis of the phase of FKOs is useful to reduce ambiguity in estimating the electric-field strength. However, the line shape of the FKOs from the i-GaAs/ n-GaAs structure has not been discussed in detail though such a structure has been employed in many studies.…”
Section: Introductionmentioning
confidence: 88%
“…23 In addition, the phase of FKOs originating from the buried interface shifts strongly with the change of the epilayer thickness due to an interference effect. 24 We therefore used these peculiarities of the spectra to disclose the origin of FKOs. Let us consider in more detail the PR results for samples 1807, 1794, and 1795 given in Fig.…”
Section: A Pr Spectramentioning
confidence: 99%
“…No significant effect is detected on the electric field value. Next, we a priori assume that phase does not depend a lot on the temperature, following previous studies 4 which have shown that it essentially depends on optical interferences, which hardly depend on temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Photoreflectance ͑PR͒ spectroscopy has been used to characterize semiconductor heterostructures and a number of device structures such as heterojunction bipolar transistors ͑HBT͒, [1][2][3][4] high electron mobility transistors, 5,6 and quantum well lasers. 7 Because of its derivative-like nature a large number of sharp spectral features can be observed, even at room temperature, and it is possible to determine the energy and broadening parameter of any direct interband transition.…”
Section: Introductionmentioning
confidence: 99%